9 - Book Reviews: Rose W. Gaciabu, De-feminization of Poverty in Africa: Are We Keeping the Promise? Nairobi, Catholic University of Eastern Africa, 1996,43p.: by Hannington Ochwada - Hannington Ochwada (Africa Development, 1997)
Abstract